ANALISA STABILITAS LERENG DENGAN PERKUATAN SOIL NAILING MENGGUNAKAN PROGRAM GEOSLOPE - Nofrizal, Nofrizal; Refi, Ahmad; Farhan, Muhammad (Ensiklopedia of Journal, 2024)
A slope is a surface that connects higher land with a lower land surface, and slope stability is closely related to landslides or ground movement which is the process of natural movement of soil masses from higher to lower areas. (Korach et al, 2014). Soil stability on slopes can be disturbed due to the influence of several things, such as nature, climate and human activities. This disturbance can cause landslides which occur due to an imbalance in the forces acting on the slope or the force in the slope area is greater than the supporting force on the slope. Several factors cause landslides, namely slopes that are too straight, climate, inadequate soil properties, insufficient compaction, the influence of groundwater and rain, earthquakes and also human activity. The damage caused by landslides is not only direct but also indirect damage which hampers economic activities and development. The objective to be achieved in this research is to determine the value of the safety factor for natural slopes based on landslide analysis using the geoslope program. And look for the crisis intensity value that causes slope failure. From the research, it was concluded that the Factor of Safety (FoS) value of the slope using the Geoslope/W 2012 software, at a slope angle of 30 0 without reinforcement was 0.275, and at a slope angle of 45 0 without reinforcement it was 0.204. By using Geoslope/W 2012 software with nail installation on the slope, at a slope angle of 30 0 the FoS value was obtained at 1.067, and at a slope angle of 45 0 the FoS value was obtained at 1.222.Keywords: slope, landslide, factor of safety